Formation of gas‐phase peptide ions and their dissociation in MALDI: Insights from kinetic and ion yield studies. Issue 2 (26th May 2014) - Moon, Jeong Hee; Yoon, Sohee; Bae, Yong Jin; Kim, Myung Soo
<x xml:space="preserve">Abstract</x> Insights on mechanisms for the generation of gas‐phase peptide ions and their dissociation in matrix‐assisted laser desorption ionization (MALDI) gained from the kinetic and ion yield studies are presented. Even though the time‐resolved photodissociation technique was initially used to determine the dissociation kinetics of peptide ions and their effective temperature, it was replaced by a simpler method utilizing dissociation yields from in‐source decay (ISD) and post‐source decay (PSD). The ion yields for a matrix and a peptide were measured by repeatedly irradiating a region on a sample and collecting ion signals until the sample in the region was completely depleted. Matrix‐ and peptide‐derived gas‐phase cations were found to be generated by pre‐formed ion emission or by ion‐pair emission followed by anion loss, but not by laser‐induced ionization. The total number of ions, that is, matrix plus peptide, was found to be equal to the number of ions emitted from a pure matrix. A matrix plume was found to cool as it expanded, from around 800−1, 000 K to 400−500 K. Dissociation of peptide ions along b/y channels was found to occur statistically, that is, following RRKM behavior. Small critical energy (E0 = 0.6–0.7 eV) and highly negative critical entropy (ΔS‡ = −30 to −25 eu) suggested that the transition structure was stabilized by multiple intramolecular interactions. © 2014 Wiley Periodicals, Inc. Mass Spec Rev 34: 94–115, 2015.